COMPARISON OF STUDY HABITS OF CLASS 10 STUDENTS OF GOVERNMENT AND PRIVATE SCHOOLS IN FARIDABAD DISTRICT - Kumari, Kiran; Gaud, Poonam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the current study, study habits are defined as the techniques, approaches, and routines that students adopt to enhance their learning and understanding. The primary objective of this study is to conduct a comparative analysis of the study habits of Class 10 students from government and private schools in Faridabad district. The comparative survey method was used within the descriptive research methodology. The study population consisted of Class 10 students. A random sampling technique was used to select the sample, resulting in 400 students (from both government and private schools). The study habits inventory developed by Dr. Deepti Sharma and Dr. Masood Ansari was used for data collection. The collected data was analyzed using statistical techniques such as mean, standard deviation, and t-test. The results of the study indicate that there were significant differences in the study habits of students from government and private schools. However, when the study habits were classified by gender, no significant differences were observed between the two groups. In conclusion, this research indicates that study habits are influenced by a number of complex factors, including self-perception, individual versus group study preferences, study methods used, content structure, and mental state. Thus, this research underscores the need to develop educational strategies that address learners’ needs while taking into account individual differences and diverse learning environments.